Systematic Exploration of a Catalytic Metal–Organic Framework/Polyurethane Composite for Medical Device Applications: Effects of MOF Particle Size, MOF Loading, and Polymer Concentration on Composite Material Activity - Melvin, Alyssa C.; Reynolds, Melissa M. (Frontiers in Physics, 2022)
The metal–organic framework (MOF) CuBTTri, H3[(Cu4Cl)3(BTTri)8] (where H3BTTri = 1,3,5-tris(1H-1,2,3-triazol-5-yl)benzene), is a promising catalyst for the development of antithrombotic medical device materials via localized nitric oxide (NO) generation from endogenous S-nitrosothiols. This work evaluates the effects of three key parameters of CuBTTri-embedded polyurethane composite materials—MOF preparation/particle size, MOF loading, and polymer concentration—on the rate of NO generation. We discovered that CuBTTri preparation and particle size have a significant impact on NO generation. Specifically, hand-ground MOF particles (0.3 ± 0.1 µm diameter) generate NO at greater rates compared to larger as-prepared, raw MOF particles (0.4 ± 0.2 µm diameter) and smaller, filtered MOF particles (0.2 ± 0.1 µm diameter) for composite materials. This finding contradicts previous research for CuBTTri powder which found that the smaller the particles, the greater the catalytic rate. In examining the effects of MOF loading and polymer concentration, our data show that increasing these parameters generally results in increased rates of NO generation; though thresholds appear to exist in which increasing these parameters results in diminishing returns and impedes NO generation capacity for certain composite formulations. We found that polymer concentration is the key determinant of water absorptivity and statistically significant decreases in water uptake accompany statistically significant increases in NO generation. It was also found that formulations with relatively high MOF loadings and low polymer concentrations or low MOF loadings and high polymer concentrations inhibit the rate of NO generation. In summary, this research provides a framework for more strategic selections of key parameters when fabricating composite materials for medical device applications.